A SiW11Mn-assisted indium electrocatalyst for carbon dioxide reduction into formate and acetate. Issue 38 (May 2020) - Li, Chunxiang; Zha, Bingjie; Li, Jinjin
Graphical abstract: Highlights: SiW11 Mn-assisted metal In electrocatalyst converted CO2 to acetic and formic. The system overcomed the low selectivity limitation of In for C2 products. The faradaic efficiency is 72.1% for acetic acid. Abstract: Electrochemical reduction of CO2 is an attractive technique for reducing CO2 emission and converting it into valued commodity chemicals. Most of catalysts such as metal In exhibit selectivity towards formation of C1 products, whereas C2 products suffer from high overpotential, low efficiency or poor selectivity. Here, polyoxometalate (SiW11 Mn)-assisted metal In was proposed as an efficient electrocatalyst for electrochemical reduction of CO2 into acetic acid and formic acid with Faradaic efficiencies of 72.1 % and 6.1 % respectively. It overcomed the low selectivity limitation of In for C2 products, converting CO2 to acetic acid over formic acid with an onset potential of −0.8 V vs. Ag/AgCl (−0.35 vs RHE). The superior selectivity of the SiW11 Mn-assisted In catalyst studied herein maybe originates from SiW11 Mn effect.